Sanitary and hygienic issues in the design of individual heat supply systems - A. L. Toropov (Vestnik MGSU)
Introduction. In the case of individual construction, the existing design standards for district heating systems are of a reference nature. The owner of the household determines how much hot water he needs, what the temperature in the room should be. It is important that fire safety, environmental standards, sanitary standards and standards of energy allocated per household are not violated. The parameters of HWS are quantitative. There are questions about the quality of sanitary water that has contact with human skin. There are engineering solutions that can eliminate or significantly reduce these risks. It is advisable to apply these engineering solutions at the design stage.Materials and methods. Based on the generalization of data from scientific sources and published cases of mass diseases, the main types of pathogenic bacteria occurring in individual water and heat supply systems were identified. These are Legionella and Pseudomonas aeruginosa. The thresholds and conditions of viability of these bacteria are considered. The main causes that cause the risks of growth of pathogenic bacteria are classified.Results. Requirements of observance of complex technical measures at designing consist in necessity of selection of the equipment of systems of individual heat supply at observance of conditions of control of water intake, maintenance of preliminary heating of water up to temperature 65 °С in systems of accumulation type, constant circulation of water in circuits of water supply, use of flowing water heaters, selection of pipes.Conclusions. The use of technical solutions for heat supply systems of individual construction facilities can significantly reduce or completely eliminate the risks associated with the possibility of pathogenic bacteria and diseases of people living in households.